Extracts from the Cochrane Library: "Grommets (ventilation tubes) for hearing loss associated with otitis media with effusion in children". - Burton, M; Derkay, C; Rosenfeld, R (2011)
The Cochrane Corner is a quarterly section in the journal that highlights systematic reviews relevant to otolaryngology–head and neck surgery, with invited commentary to aid clinical decision making. This installment features an updated Cochrane review "Grommets (Ventilation Tubes) for Hearing Loss Associated with Otitis Media with Effusion in Children" that reinforces the modest benefits demonstrated in the original review published in 2005.